Lack of serum‐ and glucocorticoid‐inducible kinase 3 leads to podocyte dysfunction. Issue 2 (4th January 2018) - Peng, Li‐Qin; Zhao, Hong; Liu, Song; Yuan, Ya‐Pei; Yuan, Cheng‐Yan; Mwamunyi, Mercy‐Julian; Pearce, David; Yao, Li‐Jun
Abstract : Serum‐ and glucocorticoid‐inducible kinase 3 (SGK3) is a downstream mediator of PI3K, which is essential for maintaining the functional integrity of podocytes. However, little is known about the role of SGK3 in podocyte function. Herein, we demonstrated that SGK3 contributes to the maintenance of podocyte integrity. Conditionally immortalized mouse podocyte cells (MPCs) were treated with puromycin aminonucleoside (PAN). PAN treatment inhibited the activity of SGK3 and the expression of podocin. Short hairpin RNA (shRNA)‐mediated knockdown of SGK3 also reduced podocin expression in the absence of PAN. Adriamycin (ADR)‐treated mice developed proteinuria and had decreased renal glomerular SGK3 expression in comparison to control mice. Consistent with a role for SGK3 in the ADR effect, SGK3 knockout (KO) mice had markedly reduced kidney podocin expression and significantly elevated proteinuria compared with wild‐type mice. Electron microscopy revealed that SGK3 KO mice displayed partial effacement of podocyte foot processes. Further, a SGK3 target protein, glycogen synthase kinase‐3 (GSK3), was discovered to be dramatically activated in PAN and SGK3 shRNA‐treated MPCs and in SGK3 KO mice. Taken together, these data strongly suggest that SGK3 plays a significant role in regulating podocyte function, likely by controlling the expression and activity of GSK3.—Peng, L.‐Q., Zhao, H., Liu, S., Yuan, Y.‐P., Yuan, C.‐Y., Mwamunyi, M.‐J., Pearce, D., Yao, L.‐J. Lack of serum‐ and glucocorticoid‐inducible kinase 3 leads to podocyte dysfunction. FASEB J. 32, 576–587 (2018). www.fasebj.org